2020
DOI: 10.1017/s1041610219002011
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of antipsychotic medications in long-term aged care in Australia: a snapshot from the HALT project

Abstract: Objectives:Use of antipsychotic drugs in long-term aged care (LTC) is prevalent and commonly exceeds the recommended duration, but contributors to this problem are not well understood. The objective of this study is to provide a snapshot of the features of and contributors to prolonged use of antipsychotic medications (>12 weeks) among a sample of LTC residents.Design:We present retrospective and baseline data collected for the Australian Halting Antipsychotic Use in Long-Term Care (HALT) single-arm longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…The HALT study aimed to reduce inappropriate long-term use of antipsychotics by providing education and training in appropriate and nonpharmacological management of BPSD, followed by implementation of an intervention to promote deprescribing of antipsychotics (Brodaty, 2018). The analysis of baseline data from the HALT study presented in this issue of the journal used data collected before the deprescribing intervention commenced (Harrison et al, 2020). Harrison and colleagues found that the 146 study participants had been using antipsychotics for an average of 2.2 years at baseline, which was equivalent to use for more than 80% of the time the participants had been living in aged care.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The HALT study aimed to reduce inappropriate long-term use of antipsychotics by providing education and training in appropriate and nonpharmacological management of BPSD, followed by implementation of an intervention to promote deprescribing of antipsychotics (Brodaty, 2018). The analysis of baseline data from the HALT study presented in this issue of the journal used data collected before the deprescribing intervention commenced (Harrison et al, 2020). Harrison and colleagues found that the 146 study participants had been using antipsychotics for an average of 2.2 years at baseline, which was equivalent to use for more than 80% of the time the participants had been living in aged care.…”
mentioning
confidence: 99%
“…The indication for antipsychotic initiation was documented for 90% of participants, and for three quarters of these people, the indication for initiation matched the approved indications for use in dementia. Current BPSD symptoms (experienced in the past month) were documented for 87% of participants and were most commonly aggression (81% of participants with BPSD) or irritability (72%) (Harrison et al, 2020). Sixty-two percent of participants had recommendations documented in their aged care notes by an appropriately qualified health professional to review the need for continued use of the antipsychotic (Harrison et al, 2020).…”
mentioning
confidence: 99%
See 3 more Smart Citations